Dampak Media terhadap Komunikasi Keluarga - Tyara Octaviyana; Evi Septiyani; Yara Alma Nadira; Quina Bilqis; Mia Sri Mulyani; Yani Achdiani; Sara Nurul Fatimah (Lembaga Pengembangan Kinerja Dosen, 2025)
The nation's ideals to pay attention to the number of children with Disaster Families are the paradigm of the National Family Planning Family Planning Program which in 2015 had become a Quality Family Program. The type of research in this study is an analytical observational study using case control stimuli which is used to study the extent to which risk factors influence the occurrence of an effect. This research uses a retrospective approach, by identifying causal factors in past events. The sample to be used in this study was 35 mothers who visited the Ely Midwife Clinic and participated in the 3-month injection family planning program from January to April 2022. Acceptors of 3-month injection family planning are at greater risk of experiencing greater weight gain than non-acceptors of 3-month injection family planning, so that 3-month injection family planning has a greater influence than non-acceptors of 3-month injection family planning. 3-month injection contraception is not the main factor causing weight gain, as shown by the results of the Cochran & Mantel Haenszel significance test, the results obtained were X2 count (2.089) < X2 Table (3.841) or p (0.148) > α (0.050) and CI (0.872; 6.118). The benefits of this study can be used as a consideration for further research. Through a larger number of respondents and the number of variables, such as age, food intake, lifestyle, activity, and others. Midwives and other health workers can provide counseling about the side effects of 3-month injection contraception so that there is no concern from the acceptors of the contraception